Walking Wheel Design for Lunar Rove-Rand and Its Application Simulation Based on Virtual Lunar Environment. (3rd May 2014) - Yibing, Zhao; Ronghui, Zhang; Linhui, Li; Lie, Guo; Mingheng, Zhang
Abstract : The lunar rover design is the key problem of planet exploration. It is extraordinarily important for researchers to fully understand the lunar terrain and propose the reasonable lunar rover. In this paper, one new type of walking wheel modeled on impeller is presented based on vehicle terramechanics. The passive earth pressure of soil mechanics put forward by C. A. Coulomb is employed to obtain the wheel traction force. Some kinematics simulations are conducted for lunar rover model. Besides, this paper presents how to model lunar landing terrain containing typical statistic characteristic including craters and boulders; then, the second step is to construct basal lunar surface by using Brown Fractal Motion and the next is to add craters and boulders by means of known diameter algorithm and Random-create Diameter Algorithm. By means of importing 2D plain of lunar surface into UG, 3D parasolid is modeled and finally imported to ADAMS, which is available for lunar rover kinematics and dynamics simulation. Lastly, based on power spectrum curve of lunar terrain, the spectral characteristic of three different lunar terrain roughness is educed by using reverse engineering algorithm. Simulation results demonstrated the frequency of vibration mechanics properties of different roughness surfaces.